(untitled) (Global Journal of Management and Business Research, 2017)
The purpose of this paper is to explore the different dimensions of employee empowerment and to determine the impact of employee empowerment tools on performance of private sector employees in Punjab. Structured questionnaire is used to collect the required primary data from 80 respondents in private sector in Punjab. Descriptive statistics, correlation, regression analysis, factor analysis and t-test are used as statistical tools in analysis. The study found that Performances of employees are significantly affected by independent decision making and open communication in the organization. Getting equal rights in organization is the most important factor which improves performance of the private sector employees. The first factor ’communication empowerment ’explained 25.90 percent of the total variance and it comprises five variables namely encouragement of open communication, authority to correct problem, input is solicited in planning changes and job gives sense of accomplishment.